2014
DOI: 10.3233/bmr-140478
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of restless legs syndrome in fibromyalgia syndrome: An analysis of quality of sleep and life

Abstract: Presence of RLS should be investigated in every patient with FMS and treatment plans should also cover RLS in case of coexistance with FMS. Prospective cohort studies are needed for better explanation of FMS and RLS coexistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 34 publications
0
11
1
2
Order By: Relevance
“…Although both diseases are known to be associated, differential diagnosis might be difficult in patients with severe pain in the lower extremities. The majority of patients with FM have moderate or severe RLS (39). However, no difference was detected between patients with RLS (moderate/severe/very severe) with and without FM in terms of the severity of RLS in our study.…”
Section: Discussioncontrasting
confidence: 48%
“…Although both diseases are known to be associated, differential diagnosis might be difficult in patients with severe pain in the lower extremities. The majority of patients with FM have moderate or severe RLS (39). However, no difference was detected between patients with RLS (moderate/severe/very severe) with and without FM in terms of the severity of RLS in our study.…”
Section: Discussioncontrasting
confidence: 48%
“…Various studies showed the increased frequency of RLS and its association with poor sleep quality in many diseases such as chronic renal failure, [26] fibromyalgia, [27] ankylosing spondylitis, [28] lumbar radiculopathy, [29] inf lammatory bowel disease, [30] or primary biliary cirrhosis. [31] However, there exist only a small number of studies which investigate the relationship between RLS and allergic diseases in adults, but not in children.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disorders like obstructive sleep apnea and restless legs syndrome appear to be more common in patients with FMS, particularly in male patients, than in the general population [151][152][153][154][155][156], and FMS may be more prevalent among patients with sleep apnea than in the general population [157]. The presence of such sleep disorders is associated not only with worse perceived sleep quality, but also with pain, fatigue, and greater symptoms severity (assessed with the Fibromyalgia Impact Questionnaire, FIQ) [151,156].…”
Section: Sleepmentioning
confidence: 99%